Factors associated with violent offenders with mental illness in forensic psychiatric evaluations - Chia-Heng Lin; Wen-Ching Hsieh; Li-Ting Lin; Chia-Hsiang Chan (PLoS ONE, 2025)
Purpose The overall crime rate among individuals with severe mental illnesses is similar to that of the general population, although some studies suggest a higher risk of violent crime among this group. Empirical research on factors associated with violent crime among individuals with mental illnesses in East Asia remains limited. Methods This study examined 648 offenders referred for forensic psychiatric evaluation by the criminal justice system to explore the relationship between severe mental illness, substance-related and addictive disorders, and violent crime. Demographic, clinical, forensic, and both static and dynamic factors were analyzed using bivariate analysis and multivariate logistic regression. We also tested the moderating effects of gender, history of violent crime, poor treatment adherence, and comorbid substance-related and addictive disorders on the association between severe mental illness and violent crime. Results The results showed that violent offenders were more likely to be male and to have never undergone a psychiatric evaluation prior to the offense, compared to non-violent offenders. Severe mental illness, substance-related and addictive disorders, single status, unemployment, and poor treatment adherence were not significantly associated with violent crime. Furthermore, gender, poor treatment adherence, a history of violent crime, and comorbid substance-related and addictive disorders did not significantly moderate the relationship between severe mental illness and violent crime. Conclusion These findings emphasize that individuals with severe mental illness should not be automatically linked to violent offending. A comprehensive evaluation of offenders with severe mental illness is crucial, alongside a deeper understanding of their treatment and reintegration needs.